Formation and Coloring Mechanism of Typical Aluminosilicate Clay Minerals for CoAl2O4 Hybrid Pigment Preparation - Zhang, Anjie; Mu, Bin; Wang, Xiaowen; Wen, Lixin; Wang, Aiqin (Frontiers in Chemistry, 2018)
Different kinds of aluminosilicate minerals were employed to fabricate CoAl2O4 hybrid pigment for studying its formation and coloring mechanism. It revealed that the color of the obtained hybrid pigments was determined by the content of Al2O3 and lightness of clay minerals. The higher the Al2O3 content and the lightness of clay minerals, the better the color parameters of hybrid pigments. During the preparation of hybrid pigments, CoAl2O4 nanoparticles were confined to be loaded on the surface of the aluminosilicate minerals, which effectively prevented from the aggregation and the size increase of CoAl2O4 nanoparticles. What’s more, aluminosilicate mineral might be an ideal natural aluminum source to compensate the aluminum loss due to the dissolution of Al(OH)3 at alkaline medium during precursor preparation, keeping an optimum molar ratio of Co2+/Al3+ for formation of spinel CoAl2O4 pigments in the process of high-temperature crystallization.